Geographic variation in fungal diversity associated with leaf spot symptoms of Coffea arabica in Yunnan, China - Fu, Xingfei; Yu, Haohao; Li, Yaqi; Li, Guiping; Bi, Xiaofei; Li, Yanan; Hu, Faguang; Dong, Wenjiang (Frontiers in Microbiology, 2025)
In China, the small grain coffee plants (Coffea arabica) are mainly cultivated in Yunnan province, yet the diversity of associated fungi remains poorly characterized. In this study we collected symptomatic leaves from 16 locations across Pu’er City and Xishuangbanna Dai Autonomous Prefecture (n = 48 samples, triplicate controls). Fungal communities were analyzed via ITS amplicon sequencing (Illumina MiSeq). We identified 3,638 fungal OTUs, dominated by Ascomycota (92%), including pathogens (Colletotrichum gloeosporioides, Cercospora coniogrammes), saprophytes, and beneficial entomopathogens (Lecanicillium, Simplicillium). The fungal communities showed significant geographical variation, with Pu’er City exhibiting a higher relative abundance of pathogenic fungi such as Colletotrichum gloeosporioides and Cercospora coniogrammes, while Xishuangbanna had a greater presence of beneficial entomopathogenic fungi such as Lecanicillium and Simplicillium. We classified abundant fungal OTUs into 48 different species colonizing leaves of coffee plants. Our core microbiome analysis revealed the presence of Cercospora coniogrammes (2%), the Fusarium equiseti of Nectriaceae family (5%), and the novel pathogenic fungi Colletotrichum gloeosporioides and Cercospora coniogrammes. Interestingly, we also identified the anti-phytopathogenic fungi belonging to the genus Simplicillium (9%) and entomopathogenic fungi known as lecanicillium (11%). This first report of C. coniogrammes and C. gloeosporioides in Yunnan coffee highlights the need for region-specific disease management. The prevalence of entomopathogenic fungi in Xishuangbanna suggests untapped biocontrol potential. Our data provide a foundation for monitoring leaf-associated fungi to improve crop resilience.